2018
DOI: 10.5539/ijel.v8n6p107
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Technology in English Language Teaching: Global Experiences and Lessons for Indonesia

Abstract: The integration of Information and Communication Technology (ICT) in English language educational settings often improves teaching and learning (Tinio, 2016). English language teaching and technology have been seen as interesting new research era. This article reviewed studies on ICT integration in teaching from ten different countries. The aim of this review is to analyze cross cultural findings in order to determine what factors might be best applied to the Indonesia situation to improve English language lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…Meskipun pemerintah telah berupaya untuk menfasilitasi sekolah-sekolah dengan perangkat teknologi, namun banyaknya jumlah sekolah yang membutuhkan dukungan infrastruktur teknologi menyebabkan belum meratanya dukungan dari pemerintah, sehingga tidak mengherankan ketika masih sangat jarang, bahkan tidak pernah digunakannya produk teknologi sebagai media untuk mendukung pembelajaran baik didalam maupun diluar kelas. Tidak dapat dipungkiri bahwa pengunaan teknologi bukanlah suatu strategi yang dapat diimplementaskan dengan mudah, melainkan membutuhkan kesabaran dan penyesuaian terkait dengan kurikulum, kondisi sekolah, kompetensi guru, fakto keuangan sekolah, (Ammade, Mahmud, Jabu, & Tahmir, 2018). Berdasarkan data yang diperoleh, berkisar 60%-70% siswa/i yang jarang bahkan tidak pernah memiliki pengalaman belajar dengan menggunakan perangkat teknologi diatas sebagai media belajar mereka.…”
Section: Hasil Dan Pembahasan a Penggunaan Media Pembelajaran Pada Punclassified
“…Meskipun pemerintah telah berupaya untuk menfasilitasi sekolah-sekolah dengan perangkat teknologi, namun banyaknya jumlah sekolah yang membutuhkan dukungan infrastruktur teknologi menyebabkan belum meratanya dukungan dari pemerintah, sehingga tidak mengherankan ketika masih sangat jarang, bahkan tidak pernah digunakannya produk teknologi sebagai media untuk mendukung pembelajaran baik didalam maupun diluar kelas. Tidak dapat dipungkiri bahwa pengunaan teknologi bukanlah suatu strategi yang dapat diimplementaskan dengan mudah, melainkan membutuhkan kesabaran dan penyesuaian terkait dengan kurikulum, kondisi sekolah, kompetensi guru, fakto keuangan sekolah, (Ammade, Mahmud, Jabu, & Tahmir, 2018). Berdasarkan data yang diperoleh, berkisar 60%-70% siswa/i yang jarang bahkan tidak pernah memiliki pengalaman belajar dengan menggunakan perangkat teknologi diatas sebagai media belajar mereka.…”
Section: Hasil Dan Pembahasan a Penggunaan Media Pembelajaran Pada Punclassified
“…Finding the articles through search-engine were a little bit difficult for the writers because some criteria that suitable with the aims of this paper must be set up before findings / collecting the materials. Therefore, adapting some specific criteria from Ammade et al (2018), it was designed to avoid misleading in finding the materials, which as follow: 1. The articles must be an empirical research in which such technology used in the English language teaching and learning was explicitly described in the article; 2.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, the writers are interested in identifying and analyzing the documented research articles on the topic of the use of technology in ELT worldwide. Some of previous research such as (Ürün, 2016;Ammade et al, 2018;Halim and Hashim, 2019;Shadiev and Yang, 2020). These previous research took a chronological research on technology integration based on its' year published.…”
Section: Introductionmentioning
confidence: 99%
“…A review of recent research on technology-supported teaching reveals a number of important points. For example, Ammade et al (2018) proposed that technology integration in the classroom plays a positive role in creating a student-oriented teaching and learning process so that it can help F improve student activity and thought processes. In addition, Ghavifekr et al (2016) also found in his study that technological integration has benefits for student motivation and can increase student confidence.…”
Section: B Review Of Literaturementioning
confidence: 99%